Reading is essential to our mental wellbeing / Muhamad Izzat Rahim - Rahim, Muhamad Izzat (UiTM Cawangan Negeri Sembilan, 2022)
The internet is altering the way we think and behave. For one, it makes us impatient as we crave instant results or gratifications. This is unavoidable since the internet has made our world move faster than before. The need for instant results or gratifications has seeped into our daily chores and activities. For example, nowadays we expect same-day-delivery services for our purchases. We also expect the result of an examination or an interview to be provided instantly. These examples show that as a society we have become more impatient and less tolerant. This situation has brought about negative effects on the people. People become easily frustrated when their expectations for fast and instant results are unmet. This could lead to other serious mental health issues such as anxiety, stress, and being ill-tempered. Furthermore, people would become less tolerant of others as they only focus on their needs.